(3cTa GdOjf aj CMhGd GdYjfs - (3eMeO Hf EHQGgje Hf SGYO GdGfUGQj GdSfLGQj, hjYQa HGHf GdCcaGfj, CHh YHO Gddg,J (B749 (3g` s ((3YeQGf GHf eMeO Hf CHj GdfhQ GdZQjGfi s)
(3ChdgG (B:s
(3hHYO aEfi LGeY gPG GdcJGH ai UfGYI GdcMd , hQJHg Ydi KdGK ebGdGJ s
(3BNQgG (B:s
(3eMehOg QHY LRA hRgQ HfaSLi KdGK GLRGA , jLeY HYSd eYbhO hdjcf gPG BNQ GdcJGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B200s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdcJGH (B- (3bSe GdcJGH GdChd (B- (3U (B156 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1490s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH (B87) s
Keywords: (3GdWHs